Implementasi Konsep Tazkiyyatun Nafsi Imam Al-Ghazali dalam Kitab Ihya’u Al-Ulumuddin dan Teknik Self-Management Terhadap Kebermaknaan Hidup Residen Pecandu Narkoba - Clauradita Angga Renny; Maemonah Maemonah (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2020)
The problem that will be faced by resident drug addicts is when they have left the rehabilitation center and returned to the community. Like being ostracized, the negative stigma from society with the negative stigma they get, resident drug addicts experience discrimination from various parties, even though they have stopped using drugs. One of the causes of drug abuse is that there is no meaningful life in the individual so that someone is very vulnerable to falling into negative things such as being oriented to drug seeking. This study aims to provide an overview of how to grow the meaning of life of drug addict residents in the after care program by using the concept of Tazkiyyatun nafs Imam Al-Ghazali in self-management techniques. The method used in this research is the library research method and literature study which is carried out by analyzing from various reference sources and drawing a sharp and critical analysis so that it can provide a rational and logical picture. This method is carried out by taking several references related to the view of tazkiyyatun an nafs and Self-Management from several reference books, journal references and other scientific articles.